Mpox Vaccine Hesitancy Among Brazilian Men Who Have Sex with Men: A National Cross-Sectional Study - Guilherme Reis de Santana Santos; Caíque Jordan Nunes Ribeiro; José Flávio Cerqueira dos Santos Júnior; Valdemar Silva Almeida; Rita de Cassia Dias Nascimento; Nilo Manoel Pereira Vieira Barreto; Anderson Reis de Sousa; Márcio Bezerra-Santos; Lariane Angel Cepas; Ana Paula Morais Fernandes; Isabel Amélia Costa Mendes; Aires Garcia dos Santos Júnior; et al. (Vaccines)
Background: Mpox is a viral zoonosis that has gained increased attention due to a global outbreak in 2022, significantly impacting men who have sex with men (MSM). Vaccination for this disease poses a public health challenge; because it carries a strong stigma, there may be greater hesitancy in vulnerable groups. Objectives: This study aimed to determine the prevalence and factors associated with Mpox vaccine hesitancy among Brazilian MSM. Methods: A cross-sectional study was conducted between September and December 2022 using an online survey targeted at MSM. Recruitment was carried out through social media and dating apps. The sample consisted of 1449 participants and the analysis involved bivariate logistic regression. Results: The prevalence of Mpox vaccine hesitancy was 7.57%. The significant factors associated with hesitancy were primarily related to sexual practices and attitudes towards Mpox exposure and diagnosis, such as not using “glory holes” (aOR: 19.82; 95% CI: 1.60–245.69), reluctance to undergo pre- and post-exposure testing for Mpox (aOR: 9.54; 95% CI: 5.52–16.48), and not knowing close contacts diagnosed with Mpox (aOR: 4.09; 95% CI: 1.72–9.73). Participants who would not take precautions after diagnosis (aOR: 3.00; 95% CI: 1.27–7.07) and those who would not disclose their serological status (aOR: 1.93; 95% CI: 1.13–3.30) also showed a higher likelihood of vaccine hesitancy. Conclusion: Public health strategies should address these factors to expand knowledge about vaccination barriers, plan educational campaigns with targeted messaging for the MSM population, and provide inclusive healthcare environments to increase vaccine acceptance and reduce Mpox transmission in vulnerable groups.